Pathological findings in stranded harbor porpoises (Phocoena phocoena) with special focus on anthropogenic causes - IJsseldijk, Lonneke L.; Leopold, Mardik F.; Begeman, Lineke; Kik, Marja J. L.; Wiersma, Lidewij; Morell, Maria; Bravo Rebolledo, Elisa L.; Jauniaux, Thierry; Heesterbeek, Hans; Gröne, Andrea (Frontiers in Marine Science, 2022)
Humans impact natural systems at an unprecedented rate. The North Sea is one of the regions in the world with the highest level of anthropogenic activities. Here, the harbor porpoise (Phocoena phocoena) is an abundant species and often regarded as ecosystem sentinel. A post-mortem surveillance program was established in the Netherlands aimed at increasing knowledge on the effects of human activities on harbor porpoises. In this study, we describe the pathological findings related to anthropogenic and natural causes of death categories in 612 harbor porpoises that stranded between 2008 and 2019, and assess relations to age, sex, season and location. The largest anthropogenic category was bycatch (17%), with mainly juveniles affected and peak periods in March and September-October. Other, infrequently diagnosed anthropogenic causes of death were trauma (4%), largely most likely due to ship collision, and marine debris ingestion and entanglement (0.3%). The risk of dying from anthropogenic causes was highest for juveniles. Lesions compatible with noise-induced hearing loss were investigated in carcasses which were fresh enough to do so (n=50), with lesions apparent in two porpoises. Non-direct human-induced threats included infectious diseases, which was by far the largest cause of death category (32%) and affected mainly adults. Also, grey seal (Halichoerus grypus) attack was a frequently assigned cause of death category (24%). There were more acute predation cases in the earlier study years, while porpoises with lesions that suggested escape from grey seal attacks were diagnosed more recently, which could suggest that porpoises adapted to this threat. Our study contributes to understanding porpoise health in response to persisting, new, emerging and cumulative threats. Building up such knowledge is crucial for conservation management of this protected species.